Analysis Of Active Billing Actions In Disclosing Tax Arrears At The Pratama Tax Service Office City Field - Wan Adinda Irva Amelia; Zulia Hanum (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study was to identify and analyze the act of active billing in the disbursement of tax arrears at KPP Pratama Medan Kota. To find out and analyze the factors that cause the low amount of active tax collection realization is not proportional to the amount of arrears at KPP Pratama Medan City. In this study using a descriptive approach. The type of data collected is quantitative. Sources of data used are primary and secondary data. Data collection techniques using interviews and documentation. The results of this study indicate that the act of active tax collection has not been achieved every year. And with a low collection target amount not proportional to the amount of tax arrears balance, it turns out that the active collection action in disbursing tax arrears has not gone smoothly. Factors causing the low number of active billing realizations are caused by internal factors and external factors.